Teaching to Express Subjective Assessment of PedagogicalPsychological Characteristics of Preschool Children. - Akbarova Zukhro Akmalzhonovna; Topvoldiyeva Fotimakhon Ravshan kizi (Zien Journals, 2023)
In this article, pedagogical and psychological characteristics of children in the fifth year of life are organized. Also, recommendations regarding the expression of subjective assessment in children of preschool age are explained on a theoretical basis
Keywords: subjective assessment; speech communication; preschool education